Importance of Fine Control of Se Flux for Improving Performances of Sb2Se3 Solar Cells Prepared by Vapor Transport Deposition. Issue 8 (11th July 2021) - Kim, Jekyung; Ji, Seunghwan; Jang, Yuseong; Jeong, Giuk; Choi, Jiwoon; Kim, Daehan; Nam, Sung-Wook; Shin, Byungha
Abstract : Sb2 Se3 possesses a quasi‐1D (Q1D) structure, which creates an anisotropic charge transporting behavior in which the carrier transport is very efficient along the Q1D direction, which is beneficial for solar cells as long as the absorber is properly aligned along the preferred orientation. However, Sb2 Se3 is prone to form donor‐like defects, such as VSe, that are detrimental to the performance. Therefore, both growth of Sb2 Se3 along the preferred orientations and the suppression of the formation of VSe are crucial in achieving Sb2 Se3 solar cells with a high efficiency. Herein, the importance of fine control of the extra supply of Se during the deposition of Sb2 Se3 in controlling crystallographic orientations and the population of VSe in the Sb2 Se3 films is described. This control determines the performance of the resulting solar cells in a superstrate configuration with a CdS buffer. Incorporation of Se during the growth resulted in a larger open‐circuit voltage due to the passivation of VSe . However, an excess supply of Se disrupts the favorable orientation by selenizing the top region of the CdS, and therefore degraded the short‐circuit current. Through the optimization of the extra supply of Se vapor, the power conversion efficiency is improved from 3.7% to 5.2%. Abstract : The promotion of the preferred [221]‐orientation and reduction of the VSe are achieved by a controlled flux of Se vapor during the deposition of Sb2 Se3 by vapor transport deposition, which results in improving performances. Herein, the importance of an optimal supply of extra Se flux in growing high‐quality Sb2 Se3 films is demonstrated.